THE INFLUENCE OF GREEN MARKETING STRATEGY ON CONSUMER DECISIONS TO PURCHASE GARDENING KIT ON IJOY.YO DURING THE COVID-19 PANDEMIC - EFFY YUSWITA; SINTIA FAUZIA; NOVI HARYATI (CV KULTURA DIGITAL MEDIA, 2023)
The green marketing strategy is believed to be able to increase integration through environmental issues in all business activities. This research aims to determine the implementation of green marketing strategies on Ijoy.yo during the COVID-19 Pandemic, to analyze the effect of green marketing strategies (green product, green price, green place, green promotion) on consumer decisions in buying gardening kit products at Ijoy. yo during the COVID-19 pandemic, to analyze the variables that have the most dominant influence on purchasing decisions for gardening kit products at Ijoy.yo during the COVID-19 pandemic. This research uses a quantitative approach. The research was conducted in February – April 2021 at Ijoy.yo. Determination of the sample using a simple random sampling technique. The research respondents were 172 consumers of Ijoy.yo. Data collection in the study was carried out using a questionnaire. Researchers analyzed the effect of green marketing strategy on gardening kit purchasing decisions using multiple linear regression analysis. The results showed that the green product, green price, green place, and green promotion variables had a simultaneous effect on the purchasing decision variables. The results of the study partially show that the green product, green price, and green promotion variables have a significant effect on the purchasing decision variables. While the green place variable has no significant effect on the purchasing decision variables. The dominant variable in this study is the green price.